Electrochemical performance of amorphous and anatase TiO2 nanotube array-based anodes fabricated by atomic layer deposition. (May 2015) - Panda, S. K.; Shin, H.
Abstract : Atomic layer deposition onto highly porous anodic aluminium oxide templates was used to fabricate the arrays of TiO2 nanotubes. The as-prepared nanotubes were amorphous and subsequently transformed to crystalline phase, anatase, by thermal annealing at the temperature of 400–500 °C. These nanotube arrays were used for Li-ion storage as anode materials. A comparative study for the electrochemical performance of amorphous and crystalline anatase nanotube-array-based anodes has been presented. Amorphous nanotube-array-based anodes showed very high irreversible capacity compared to the anatase ones. Reversible capacity of ∼177 mAh/g was achieved from anatase nanotube-array-based anode, which was close to the maximum obtainable capacity, known as maximum theoretical capacity from bulk anatase phase reported.